Peningkatan Gerak Dasar Lokomotor dengan Sirkuit Game pada Siswa Kelas II SD Negeri 8 Pakis Surabaya - Erinda Ayu Candra; Vega Chandra Dinata; Retno Mundi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Games as an alternative that helps to improve locomotor movements in children because there are fun movement tasks, one of which is by applying circuit games in improving the basic locomotor movement skills of students in class II SDN 8 Pakis 8 Surabaya students experience an increase in locomotor movement skills (walking, running jumping), this research is a class action research where in this study using 2 cycles conducted for 2 meetings. The subjects in this study were class II C SDN 8 Pakis students totaling 20 students. The techniques used in data collection are tests, observation and documentation. Based on the results of the study, it shows that through circuit games it can improve the learning outcomes of locomotor basic movements (walking, running jumping) in class II SDN 8 Pakis Surabaya This can be seen from the percentage of completeness of learning outcomes in cycle 1 and cycle 2 increased, with a percentage of completeness of 50% in cycle 1 and a percentage of completeness of 97% in cycle 2.